Surgical repair for common arterial trunk with pulmonary dominance, hypoplasia of ascending aorta, and interrupted aortic arch - Sachin Talwar; Bharat Siddharth; Saurabh Kumar Gupta; Amolkumar Bhoje; Shiv Kumar Choudhary (Annals of Pediatric Cardiology, 2019)
The arrangement of aortic and pulmonary pathways is extremely variable in the hearts with a common arterial trunk. Almost always, interruption of the aortic arch is seen in the setting of hypoplasia of the ascending aorta and dominance of the pulmonary circulation. This subset poses substantial challenges in surgical repair and portends poor outcomes. In this report, we briefly describe the technique of ascending aorta reconstruction and other aspects of the surgical repair of this rare malformation.